QTL Mapping by Whole Genome Re-sequencing and Analysis of Candidate Genes for Nitrogen Use Efficiency in Rice - Yang, Xinghai; Xia, Xiuzhong; Zhang, Zongqiong; Nong, Baoxuan; Zeng, Yu; Xiong, Faqian; Wu, Yanyan; Gao, Ju; Deng, Guofu; Li, Danting (Frontiers in Plant Science, 2017)
Nitrogen is a major nutritional element in rice production. However, excessive application of nitrogen fertilizer has caused severe environmental pollution. Therefore, development of rice varieties with improved nitrogen use efficiency (NUE) is urgent for sustainable agriculture. In this study, bulked segregant analysis (BSA) combined with whole genome re-sequencing (WGS) technology was applied to finely map quantitative trait loci (QTL) for NUE. A key QTL, designated as qNUE6 was identified on chromosome 6 and further validated by Insertion/Deletion (InDel) marker-based substitutional mapping in recombinants from F2 population (NIL-13B4×GH998). Forty-four genes were identified in this 266.5-kb region. According to detection and annotation analysis of variation sites, thirty-nine genes with large-effect single-nucleotide polymorphisms (SNPs) and large-effect InDels were selected as candidates and their expression levels were analyzed by qRT-PCR. Significant differences in the expression levels of LOC_Os06g15370 (peptide transporter PTR2) and LOC_Os06g15420 (asparagine synthetase) were observed between two parents (Y11 and GH998). Phylogenetic analysis in Arabidopsis thaliana identified two closely related homologues, AT1G68570 (AtNPF3.1) and AT5G65010 (ASN2), which share 72.3% and 87.5% amino acid similarity with LOC_Os06g15370 and LOC_Os06g15420, respectively. Taken together, our results suggested that qNUE6 is a possible candidate gene for NUE in rice. The fine mapping and candidate gene analysis of qNUE6 provide the basis of molecular breeding for genetic improvement of rice varieties with high NUE, and lay the foundation for further cloning and functional analysis.